Advancing heart health in North Carolina primary care: the Heart Health NOW study protocol. (December 2015) - Weiner, Bryan; Pignone, Michael; DuBard, C.; Lefebvre, Ann; Suttie, Janet; Freburger, Janet; Cykert, Samuel
Abstract Background The objective of Heart Health NOW (HHN) is to determine if primary care practice support—a comprehensive evidence-based quality improvement strategy involving practice facilitation, academic detailing, technology support, and regional learning collaboratives—accelerates widespread dissemination and implementation of evidence-based guidelines for cardiovascular disease (CVD) prevention in small- to medium-sized primary care practices and, additionally, increases practices' capacity to incorporate other evidence-based clinical guidelines in the future. Methods/design HHN is a stepped wedge, stratified, cluster randomized trial to evaluate the effect of primary care practice support on evidence-based CVD prevention, organizational change process measures, and patient outcomes. Each practice will start the trial as a control, receive the intervention at a randomized time point, and then enter a maintenance period 12 months after the start of the intervention. The intervention will be randomized to practices in one of four strata defined by region of the state (east or west) and degree of practice readiness for change. Seventy-five practices in each region with a high degree of readiness will be randomized 1:1:1 in blocks of 3 sometime prior to month 8 to receive the intervention at month 9, 11, or 12. An additional 75 practices within each region that have a low degree of readiness or are recruited later will be randomized 1:1 in blocks of 2 prior to month 13 to receive the intervention at month 14 or 16. The sites will be ordered within each strata based on time of enrollment with the blocking based on this ordering. Evaluation will examine the effect of primary care practice support on (1) practice-level delivery of evidence-based CVD prevention, (2) patient-level health outcomes, (3) practice-level implementation of clinical and organizational changes that support delivery of evidence-based CVD prevention, and (4) practice-level capacity to implement future evidence-based clinical guidelines. Discussion Results will indicate whether primary care practice support is an effective strategy for widespread dissemination and implementation of evidence-based clinical guidelines in primary care practices. Discernible reductions in cardiovascular risk in 300 practices covering over an estimated 900, 000 adult patients would likely lead to prevention of thousands of cardiovascular events within 10 years. Trial registration ClinicalTrials.govNCT02585557